Annual Meeting of the International Society of Cancer Metabolism (ISCaM): Metabolic Adaptations and Targets in Cancer - Avnet, Sofia; Baldini, Nicola; Brisson, Lucie; Pedersen, Stine Falsig; Porporato, Paolo E.; Sonveaux, Pierre; Szabadkai, Gyorgy; Pastorekova, Silvia (Frontiers in Oncology, 2019)
The metabolism of cancer cells differs from that of their normal counterparts in a spectrum of attributes, including imbalances in diverse metabolic arms and pathways, metabolic plasticity and extent of adaptive responses, levels and activities of metabolic enzymes and their upstream regulators and abnormal fluxes of metabolic intermediates and products. These attributes endow cancer cells with the ability to survive stressors of the tumor microenvironment and enable them to landscape and exploit the host terrain, thereby facilitating cancer progression and therapy resistance. Understanding the molecular and physiological principles of cancer metabolism is one of the key prerequisites for the development of better anticancer treatments. Therefore, various aspects of cancer metabolism were addressed at the 5th annual meeting of the International Society of Cancer Metabolism (ISCaM) in Bratislava, Slovakia, on October 17-20, 2018. The meeting presentations and discussions were traditionally focused on mechanistic, translational and clinical characteristics of metabolism and pH control in cancer, at the level of molecular pathways, cells, tissues and organisms. In order to reflect major healthcare challenges of the current era, ISCaM has extended its scope to metabolic disorders contributing to cancer, as well as to opportunities for their prevention, intervention and therapeutic targeting.